Legitimacy and cooperation with the police: examining empirical relationship using data from Africa - Boateng, Francis D. (Policing and society, 2022)
In recent times, police legitimacy has received extensive scholarly attention among policing scholars. However, despite this attention, the controversy regarding key predicting factors of this concept is far from over. Thus, the debate about the relative predictive powers of the process-based indicators and instrumental variables is an unsettled issue. The current study analyzed comparative data from two African countries (South Africa and Sierre Leone) to test the argument that police effectiveness will have the greater influence on citizens’ assessment of the legitimacy of their local police department than will procedural justice. The study further examined the relationship between legitimacy and cooperation, as well as the direct and indirect effects of procedural justice and effectiveness on cooperation. Using Structural Equation Modelling, we found that procedural justice and effectiveness both predicted police legitimacy, but effectiveness had the greater influence. Also, legitimacy and procedural justice positively and directly predicted willingness to cooperate with the police. These observations have important policy implications for effective police practices in Africa.